Examining youth agency in Hokkien grassroots revitalisation initiatives in Singapore - Ong, Jordan Cordell Jun Heng (Nanyang Technological University, 2023)
Existing literature on the indigenous communities has highlighted the role of youths and their contributions in language revitalisation efforts. Despite the importance of youths in language revitalisation initiatives, past agentic studies have been largely one-dimensional and sparse, with no prior research having examined youth agency in the process. This study focuses on the youth-led grassroots Hokkien revitalisation initiatives in Singapore and through the examination of the participants’ responses from a total of 213 online questionnaires administered and semi-structured interviews with four local Hokkien content creators, the study aims to elucidate the development and manifestation of youth agency and Singaporeans’ perception towards these initiatives, as it will potentially reveal whether the online initiatives can be perceived as a new way of revitalisation in Singapore. The results showed that youth agentic processes are multi-dimensional, subconscious and unintended, but with various strategies in place that contributes to Hokkien revitalisation. In addition, the participants’ responses suggest that Singaporeans are generally optimistic towards the helpfulness of the videos in the acquisition of Hokkien, particularly the older, Hokkien population. This study is the first to examine youth agency in Hokkien revitalisation initiatives in Singapore and contributes foundations to agency research in new, alternative revitalisation practices on social media platforms.